Contribution to the study and evaluation of progressive collapse for an earthquake-resistant RC frame building according to specific vertical load-bearing elements removal - عبد الهادي حسن; بسـام حويجـة; نزيه منصور (Latakia University Journal -Engineering Sciences Series, 2023)
Extreme events (terrorist attacks, earthquakes, fires, explosions, ...) pose a serious threat to the various types of important and private buildings that may be subject to such events , each of them may cause local failure, which in turn causes a chain of failure and thus collapse The entire structure or a large part of it and it is associated with great human and material losses, and this is called the progressive collapse. It is difficult to predict the amount or probability of such events, and therefore it is not practical and available to design facilities against such events by traditional methods as well as with conventional loads, as design standards at the present time seek to reduce risks and provide a minimum level of control to progressive collapse by incorporating the concept of insensitivity Establishments for localized damage with design concepts in codes, so the goal is to control consequences and not take action against the extreme event itself. The main objective of the research is to test the resistance of the special frames designed according to the Syrian Arab Code on the progressive collapse according to the standards set by DOD by removing columns in specific locations according to the recommendations and evaluating the results.